2020
DOI: 10.1136/bjsports-2020-102590
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the global economic benefits of physically active populations over 30 years (2020–2050)

Abstract: ObjectivesWe assess the potential benefits of increased physical activity for the global economy for 23 countries and the rest of the world from 2020 to 2050. The main factors taken into account in the economic assessment are excess mortality and lower productivity.MethodsThis study links three methodologies. First, we estimate the association between physical inactivity and workplace productivity using multivariable regression models with proprietary data on 120 143 individuals in the UK and six Asian countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 28 publications
1
46
0
2
Order By: Relevance
“…To achieve health benefits, it is recommended that children and adolescents aged 5–17 years participate in an average of 60 min or more moderate-to-vigorous physical activity (MVPA) per day [ 12 ]. Although the benefits of PA have been well identified, physical inactivity remains a major public health problem [ 13 , 14 ]. The Healthy Active Kids South Africa (HAKSA) 2018 report indicated that 50% of children are not meeting the recommended average of 60 min of MVPA per day [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve health benefits, it is recommended that children and adolescents aged 5–17 years participate in an average of 60 min or more moderate-to-vigorous physical activity (MVPA) per day [ 12 ]. Although the benefits of PA have been well identified, physical inactivity remains a major public health problem [ 13 , 14 ]. The Healthy Active Kids South Africa (HAKSA) 2018 report indicated that 50% of children are not meeting the recommended average of 60 min of MVPA per day [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the minimum level of physical activity recommendations (150 min of MVPA/week) would theoretically result in a reduction in working-age mortality, morbidity, and an increase in productivity, mainly through lower presenteeism and sickness absence [49]. However, occupational physical activity constitutes in general of too low intensity to have any greater impact on CRF level.…”
Section: Future Agendamentioning
confidence: 99%
“…Following PA guidelines requires different investments that are not affordable for various individuals (47,95). Despite the direct expenditure of money required to participate in some activities, related for example to the purchase of clothes, allocating a certain number of minutes per day or week exclusively to engage in PA is an investment not compatible with the routine of many (63, [96][97][98]. It is not surprising that modifying one's routine to include PA was shown to be impractical due to different reasons, such as tiresome jobs, long commutes, holding more than one job and/or also studying, and competing housework chores and/or family responsibilities (47,99).…”
Section: Economicmentioning
confidence: 99%